Comparing different data descriptors in indirect inference tests on DSGE models - Patrick Minford; Michael R. Wickens; Yongdeng Xu (Cardiff University, Cardiff Business School, 2016)
Indirect inference testing can be carried out with a variety of auxiliary models. Asymptotically these different models make no difference. However, in small samples power can differ. We explore small sample power with three different auxiliary models: a VAR, average Impulse Response Functions and Moments. The latter corresponds to the Simulated Moments Method. We find that in a small macro model there is no difference in power. But in a large complex macro model the power with Moments rises more slowly with increasing misspecification than with the other two which remain similar.
Keywords: C12; C32; C52; E1; 330; Indirect Inference; DGSE model; Auxiliary Models; Simulated Moments Method